Democracy and bureaucracy in foreign affairs and domestic policy: Citizens' survey - Democracy and bureaucracy in foreign affairs and domestic policy: Citizens´ survey - Berglund, Sten (Umeå University, 1987)
In this study the respondent had to answer questions about interest in politics, party preference, party most disliked, actual vote in the 1979 election and voting intention at a hypothetical election on the day of answering the questionnaire. There were also a number of questions on the opinion of the parties regarding: employment, equality between men and women, wage-earners´ investment fund, energy and nuclear power, schools and education, defence, taxes, aid to developing countries, child care, state control of private enterprises, and foreign affairs. The respondents had to give their opinion on different statements regarding foreign affairs, defence policy, and school issues, and also to give their idea of the opinion of the political parties regarding the same statements. In addition the study deals with the respondents opinion on how to influence political decisions, and opinion on the influence different groups and organizations have on foreign affairs, defence policy, and school issues.

Vid de statsvetenskapliga institutionerna ivid Stockholms och Umeå universitets genomfördes i slutet av 1970-talet ett projekt där syftet var att undersöka åsiktsöverensstämmelsen mellan väljare och partier i ett antal frågor. Denna delundersökning tar upp allmänhetens syn på politik och de olika parterna. I centrum för undersökningen står tre sektorer - skol-, försvars- och utrikespolitik.
Frågeformuläret innehöll frågor om respondentens intresse för politik och åsikter om politik i allmänhet; hur mycket man gillar/ogillar respektive parti; hur man placerar respektive parti på en vänster-högerskala; bästa och sämsta parti; hur man röstade i riksdagsvalet 1979 och hur man skulle rösta om det vore val idag; partier som fört bra respektive dålig politik när det gäller: sysselsättningsfrågor, frågor som rör jämställdhet mellan män och kvinnor, frågor som rör löntagarafonder, energi- och kärnkraftsfrågor, skol- och utbildningsfrågor, försvarsfrågor, skattefrågor, u-hjälpsfrågor, frågor som rör barnomsorg, frågor som rör statens inflytande över näringslivet, utrikespolitiska frågor. Därutöver ställdes frågor om den egna och de politiska partiernas inställning i ett antal utrikes-, försvars- och skolpolitiska frågor: u-landsbistånd, frihandel, Norden en kärnvapenfri zon, nedrustningsfrågor, svenskt militärt flygplanssystem, försvarets storlek, skolans mål, betyg, privata skolor, kränkningar av svenskt område. Respondenterna fick också ange hur effektiva de trodde olika aktiviteter var att påverka politiska beslut och hur man själv skulle agera för att påverka beslut i skol-, försvars- och utrikespolitiska frågor.
Demokrati och byråkrati i utrikes- och inrikespolitik: Medborgarundersökningen
Keywords: defence; försvar; voting; röstning; foreign policy; utrikespolitik; political participation; politiskt deltagande; free trade; frihandel; disarmament; nedrustning; private schools; privatskolor; defence and state security policy; försvars- och säkerhetspolitik; school policy; skolpolitik; internal politics; inrikespolitik; schools; skolor; lobbying; politisk påverkan; development aid (international); utvecklingshjälp; Educational policy; Utbildningspolitik; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap